The cyclic peptide labaditin does not alter the outer membrane integrity of Salmonella enterica serovar Typhimurium - Barbosa, Simone C.; Nobre, Thatyane M.; Volpati, Diogo; Cilli, Eduardo M. [UNESP]; Correa, Daniel S.; Oliveira, Osvaldo N. (Springer Nature, 2019)
Antimicrobial peptides are a promising class of new antibiotics with the ability to kill bacteria by disrupting their cell membrane, which is especially difficult for Gram-negative bacteria whose cell wall contains an outer layer of lipopolysaccharides (LPS). Here we show that the cyclic decapeptide Labaditin (Lo), with proven activity against the Gram-positive Staphylococcus aureus and Streptococcus mutans, is not able to kill the Gram-negative Salmonella enterica serovar Typhimurium (S.e.s. Typhimurium). We found that Lo induced significant changes in the surface pressure isotherms of Langmuir monolayers representing the Salmonella enterica serovar Typhimurium inner membrane (S.e.s. Typhimurium IM), and caused leakage in large unilamellar vesicles made with this IM lipid composition. On the basis of these results one should expect bactericidal activity against S.e.s. Typhimurium. However, Lo could not interact with a monolayer of LPS, causing no significant changes in either the surface pressure isotherms or in the polarization-modulated infrared reflection absorption spectra (PM-IRRAS). Therefore, the failure of Lo to kill S.e.s. Typhimurium is associated with the lack of interaction with LPS from the outer bacteria membrane. Our approach with distinct monolayer compositions and combined techniques to investigate molecular-level interactions is useful for drug design to fight antibiotic-resistant bacteria.